Pedagogical content knowledge of mathematics student-teachers in developing ethnomathematics-based lesson plans - Meita Fitrianawati; Mukti Sintawati; Marsigit Marsigit; Endah Retnowati (Ethnomathematics Journal, 2020)
This study aims to describe the pedagogical content knowledge (PCK) of mathematics student-teachers of Yogyakarta State University (YSU). The population is mathematics student-teachers of YSU in their seventh semester of the academic year 2017/2018 who undertook ethnomathematics. A sample of 31 students was established using the cluster random sampling technique. The research instrument is in the form of ethnomathematics lesson plans developed by the students. The result of the study shows that the students’ PCK in developing ethnomathematics lesson plans is generally at the level of growing PCK. Viewed from the material and pedagogical aspects, the students’ PCK falls at the level of growing PCK. The students’ PCK in developing the lesson plans of ethnomathematics of Prambanan Temple is at the level of growing PCK. The students’ PCK in developing the lesson plans of ethnomathematics of Yogyakarta Palace is at the level of pre-PCK. The students’ PCK in developing the lesson plans of ethnomathematics of Borobudur Temple is at the level of growing PCK.